PELATIHAN MANAJEMEN DAYA TARIK WISATA DAN TEKNIK PEMANDUAN WISATA BAGI KELOMPOK TREKKING DI DESA BELOK SIDAN PETANG BADUNG - I.N Sudiarta; N.G.A.S. Dewi; L.G.L.K. Dewi; N.M.S. Wijaya; W.C.J. Sari (Buletin Udayana Mengabdi, 2018)
The purpose of community service activities are to provide knowledge to villagers Belok Sidan particularlySadar Wisata groups and trekking group "Titi Mamah" about how to manage natural attractions and guidingtechniques of trekking activities. The training uses lecture and group discussion. Aware group travel andtrekking given materials to manage tourist attraction based on the quality of service and satisfaction andtechnique guiding that meet the expectations of tourists. The results of training activities show veryenthusiastic participants attended training and various questions were raised mainly concerned with the typeof products that can be sold and how a satisfactory rating on an ongoing basis.